THEORIES & PRACTICE. - Morey, Lloyd; Kohler, E. L. (The Accounting Review, 1940)
In the September issue of the journal The Accounting Review under the title, "Deficiencies in Federal Accounting," it was discussed, among other things, the question as to whether budget accounting should be a part of the general accounting system. The journal took the negative position on this question. The early development of governmental accounting seems to have been along lines generally similar to those of commercial accounting. It was in the Handbook of Municipal Accounting that certain distinctions were more clearly recognized. Among these was an adequate accounting for budget operations, in such form as to indicate the position of the budget at all times. This meant an accounting for encumbrances, since such items must be allowed for in order to show current budget condition. The disadvantage of this procedure came gradually to be understood, as well as the possibility of bringing the two sets of records together. By 1930 the use of a consolidated system, in which the budgetary transactions are an integral part of the general accounting system, was recognized and applied in many places. The control of budgetary operations in the general accounting system does not necessarily mean the inclusion of complete budgetary accounts in the central accounting records.